2006
DOI: 10.1038/sj.jid.5700224
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Abnormalities of CCND1 and RB1 in Primary Cutaneous T-Cell Lymphomas Suggesting Impaired Cell Cycle Control in Disease Pathogenesis

Abstract: Upregulation of cyclin D1/B-cell leukemia/lymphoma 1 (CCND1/BCL1) is present in most mantle cell lymphomas with the t(11;14)(q13;q32) translocation. However, little is known about the abnormalities of CCND1 and its regulator RB1 in primary cutaneous T-cell lymphomas (CTCL). We analyzed CCND and RB status in CTCL using fluorescent in situ hybridization (FISH), immunohistochemistry (IHC), and Affymetrix expression microarray. FISH revealed loss of CCND1/BCL1 in five of nine Sézary syndrome (SS) cases but gain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 38 publications
3
28
0
2
Order By: Relevance
“…We also found a highly recurrent region of loss within 9q13-q21. 33, present in 9 of 28 samples (32%), which was not previously reported among the common deletions in CTCL (Table 1; Fig. 1).…”
Section: Resultssupporting
confidence: 47%
See 1 more Smart Citation
“…We also found a highly recurrent region of loss within 9q13-q21. 33, present in 9 of 28 samples (32%), which was not previously reported among the common deletions in CTCL (Table 1; Fig. 1).…”
Section: Resultssupporting
confidence: 47%
“…Our results indicate that large regions of low-level copy number gains (inferred copy number between 2.4 and 3.4), likely corresponding to duplication events, are prevalent in this malignancy. Similarly, HDs were not frequently observed in our series of SS patients, and although all those identified matched well-known tumor suppressor genes (CDKN2A, CDKN2B, RB1) already described in CTCL (30,33,34), they do not occur in the highly recurrent regions of copy number loss. This suggests that they might represent sporadic events further worsening the pattern of chromosomal aberrations of the tumor cell.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, we evaluated the expression of the PTEN, RB1, and p53 tumor suppressor genes, whose expression levels are often dysregulated in T cell lymphomas (Kanavaros et al 2001, Møller et al 2002, Mao et al 2006. We only observed a decrease in the expression of p53 in the tumors from hyperthyroid animals compared with those from hypothyroid or euthyroid animals, and this result was anticipated due to its key role in hematological malignancies (Kanavaros et al 2001, Møller et al 2002.…”
Section: Figurementioning
confidence: 83%
“…Furthermore, cyclin D3 overexpression is associated with a higher proliferation rate, as well as with lower p27/KIP1 and altered p53 expression (Møller et al 2001). The positive regulation of cyclins D1 and D3 has been shown to be associated with a poor prognosis in patients with lymphoma (Zukerberg et al 1995, Kanavaros et al 2001, Mao et al 2006. Cyclin E1 is a key mediator of T-cell lymphomagenesis and regulates the transition between G1 and S phases (Hosokawa et al 1995, Karsunky et al 1999, Geisen et al 2003, Kang-Decker et al 2004); however, we observed an increase only in the mRNA expression of cyclin E in hyperthyroid animals, but we cannot rule out an increment in its protein levels at other time points.…”
Section: Figurementioning
confidence: 99%
“…These abnormalities are frequently observed in CTCL, suggesting their early involvement in disease pathogenesis [92,93]. Cyclin upregulation, including cyclinD1, and loss of RB1 have also been described [94]. As gene-expression profiling and nextgeneration sequencing technologies are used, additional pathogenic pathways, including those involving transcription factors regulating T-cell differentiation [35,36], c-MYC [95,96], RAS/RAF/MEK signaling [97], among others [90,98], may be identified in subsets of CTCL.…”
Section: Immunopathogenesismentioning
confidence: 99%